2021
DOI: 10.1093/jee/toab013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sugarcane Aphid, Melanaphis sacchari (Hemiptera: Aphididae), Population Dynamics, Feeding Injury, and Grain Yield Among Commercial Sorghum Varieties in Alabama

Abstract: The sugarcane aphid, Melanaphis sacchari (Zehntner), emerged as a severe pest of sorghum, Sorghum bicolor (L.), in Texas and Louisiana in 2013 and currently threatens nearly all sorghum production in the United States. Proper management of populations is critical as sugarcane aphid has a high reproductive potential and can rapidly damage plants, resulting in extensive yield losses. The overall objective of this work was to investigate sugarcane aphid population dynamics, and subsequent sorghum injury and grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…However, grain sorghum data from individual locations differed either according to sorghum cultivar or insecticide application. Preserved grain yield in plots treated with flupyradifurone application across all locations (except Tift Co.) confirm the findings of previous authors who worked on M. sorghi in southeastern United States (e.g., Haar et al, 2019 ; Lahiri et al, 2021 ; Pekarcik and Jacobson, 2021 ). Yields were significantly greater in Moore Co., NC compared to the other study sites.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, grain sorghum data from individual locations differed either according to sorghum cultivar or insecticide application. Preserved grain yield in plots treated with flupyradifurone application across all locations (except Tift Co.) confirm the findings of previous authors who worked on M. sorghi in southeastern United States (e.g., Haar et al, 2019 ; Lahiri et al, 2021 ; Pekarcik and Jacobson, 2021 ). Yields were significantly greater in Moore Co., NC compared to the other study sites.…”
Section: Discussionsupporting
confidence: 86%
“…Further evaluation of factors including insecticide application and host plant resistance influencing M. sorghi infestations and resulting yield losses is necessary to improve IPM strategies. The use of resistant cultivars provides a baseline of protection against M. sorghi by suppressing population growth rates, limiting injury and improving grain yield, however, the performance of these varieties is geographically variable ( Lahiri et al, 2021 ; Pekarcik and Jacobson, 2021 ). Application of foliar insecticides such as flupyradifurone (Sivanto Prime, Bayer CropScience, Research Triangle Park, NC, United States) clearly suppress M. sorghi populations ( Lahiri et al, 2021 ; Pekarcik and Jacobson, 2021 ), but the efficacy of foliar application may vary by weather conditions or geographic locations ( Lahiri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of sorghum germplasm resistant to greenbug [ Schizaphis graminum (Rondani)] found that some lines were also resistant to SCA (Armstrong et al., 2015). Multiple commercial grain sorghum hybrids with moderate‐to‐good levels of resistance have been identified for the production regions of the United States (Paudyal et al., 2019b; Pekarcik & Jacobson, 2021). However, to have durable resistance, there is a need to understand the mode of inheritance and the genes that confer resistance in these resistant sources.…”
Section: Introductionmentioning
confidence: 99%